PENGARUH DIABETES SELF MANAGEMENT EDUCATION (DSME) TERHADAP SELF-CARE PASIEN DIABETES MELITUS DI RUMAH SAKIT KOTA PALEMBANG - indaryati, sri (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2018)
Diabetes melitus (DM) is a chronic disease that requires self-care. The main problem of health care in Indonesia is the lack of optimalization on the culture of patient self-care. One program that aims to facilitate knowledge and skills for diabetes patients is self-care Diabetes Self Management Education (DSME), that based on independent nursing theory by Orem "Self-Care". This study aimed to determine the effect of knowledge post diabetes self management education (DSME) implementation to self-care on patient diabetes melitus. The study utilized quantitative post test quasi experiment design with simple random sampling technique. Total sample of intervention group which is consisted of 56 respondents who received the implementation of DSME and control group which is consisted of 44 respondents who received no implementation of DSME. The statistical analysis using Independent T test resulted significant difference in self-care patient diabetes mellitus (p=0.000<0.05) between those two groups. It is expected that health care workers facilitate the self-care of patients with type 2 diabetes mellitus through the use of DSME implementation which has been shown in improving the knowledge and self-care to prevent further complications. Keywords: Diabetes Mellitus, Diabetes Self Management  Education, Self-Care